2006
DOI: 10.2500/aap.2006.27.2874
|View full text |Cite
|
Sign up to set email alerts
|

Identification of asthma risk factors in Mexico City in an International Study of Asthma and Allergy in Childhood survey

Abstract: The International Study of Asthma and Allergy in Childhood (ISAAC) has assessed the prevalence of asthma, as well as the factors related to the disease in different countries. The aim of this study was to identify asthma risks factors in Mexico City. Data were obtained from questionnaires of children participating in a phase 3b ISAAC survey. Two thousand ninety-eight boys and 2008 girls were recruited in the 6- to 7-year-old group and 3243 boy and 3333 girls were recruited in the 13- to 14-year-old group. Logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The differences in the prevalence of both atopy and asthma due to geographical variations have been reported. A family history of asthma in firstdegree relatives, low educational level, low family income, overcrowding, smoking at home, degree of urbanization, living in large cities, and various variables related to indoor air were probably associated with respiratory symptoms (Cooper et al 2006;Del-Rio-Navarro et al 2006;Dinmezel et al 2005;Kawada 2004;McIntire et al 2004;Petronella and Conboy-Ellis 2003;Tsuang et al 2003). The process of industrialization of some cities has left a legacy of a widespread and often poorly controlled environment which is widely believed to have adverse implications for health, in particular for respiratory diseases (McIntire et al 2004;Monteil et al 2005;Petronella and Conboy-Ellis 2003).…”
Section: Discussionmentioning
confidence: 94%
“…The differences in the prevalence of both atopy and asthma due to geographical variations have been reported. A family history of asthma in firstdegree relatives, low educational level, low family income, overcrowding, smoking at home, degree of urbanization, living in large cities, and various variables related to indoor air were probably associated with respiratory symptoms (Cooper et al 2006;Del-Rio-Navarro et al 2006;Dinmezel et al 2005;Kawada 2004;McIntire et al 2004;Petronella and Conboy-Ellis 2003;Tsuang et al 2003). The process of industrialization of some cities has left a legacy of a widespread and often poorly controlled environment which is widely believed to have adverse implications for health, in particular for respiratory diseases (McIntire et al 2004;Monteil et al 2005;Petronella and Conboy-Ellis 2003).…”
Section: Discussionmentioning
confidence: 94%
“…Within the past decade several studies have suggested that early-life exposure to antibiotics is associated with the etiology of childhood asthma [9,10]. Marra et al [11] did a systematic review study and found that the pooled OR from retrospective studies was significantly stronger than the prospective studies (OR ¼ 2.85; 95%CI 2.07-3.85 versus OR ¼ 1.12; 0.88-1.42).…”
Section: Introductionmentioning
confidence: 97%
“…Asthma guidelines around the world strongly recommend that women continue their asthma medications during pregnancy to maintain adequate control [7,8,12-18]. However, women are still choosing to cease their asthma medications during pregnancy, many without consulting their doctors [19-21].…”
Section: Introductionmentioning
confidence: 99%